2021
DOI: 10.1139/cjpp-2020-0449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of casein kinase 1α inhibition on autophagy flux and the AKT/phospho-β-catenin (S552) axis in HCT116, a RAS-mutated colorectal cancer cell line

Abstract: The Wnt/β-catenin pathway, which interferes with cell proliferation, differentiation, and autophagy, is commonly dysregulated in colorectal cancer (CRC). Mutation of the RAS oncogene is the most prevalent genetic alteration in CRC and has been linked to activation of protein kinase B (AKT) signaling. Phosphorylation of β-catenin at Ser 552 by AKT contributes to β-catenin stability, transcriptional activity, and increase of cell proliferation. Casein kinase 1 alpha (CK1α) is an enzyme that simultaneously regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…To ascertain whether avasimibe exerts its protective effect on the epithelial barrier by targeting the Wnt/β-catenin signaling pathway, we detected β-catenin-related phosphorylation sites. Previous studies have shown that these phosphorylation sites contribute to β-catenin localization at the cytomembrane, stabilization at the cytoplasm and increase cell proliferation (Ponce et al, 2011;Groulx et al, 2014;Zhu et al, 2019;Behrouj et al, 2021). Interestingly, avasimibe repressed phospho-β-catenin at Ser552, Ser675, and Thr41/Ser45 and also reduced active β-catenin levels, which could repress the Wnt/β-catenin activity (Figure 6A).…”
Section: Avasimibe Lowered Proliferation Of Basal Cells By Suppressin...mentioning
confidence: 71%
“…To ascertain whether avasimibe exerts its protective effect on the epithelial barrier by targeting the Wnt/β-catenin signaling pathway, we detected β-catenin-related phosphorylation sites. Previous studies have shown that these phosphorylation sites contribute to β-catenin localization at the cytomembrane, stabilization at the cytoplasm and increase cell proliferation (Ponce et al, 2011;Groulx et al, 2014;Zhu et al, 2019;Behrouj et al, 2021). Interestingly, avasimibe repressed phospho-β-catenin at Ser552, Ser675, and Thr41/Ser45 and also reduced active β-catenin levels, which could repress the Wnt/β-catenin activity (Figure 6A).…”
Section: Avasimibe Lowered Proliferation Of Basal Cells By Suppressin...mentioning
confidence: 71%
“…It has been recently described that CK1α plays a role in upregulating the autophagy pathway in several cancer cell lines (Behrouj et al 2021;Cai et al 2018;Carrino et al 2019;Cheong et al 2015;Szyniarowski et al 2011). Furthermore, it has been suggested that CK1α overexpression, may serve as a negative prognostic marker for CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an important factor influencing chemotherapy resistance to 5-FU in CRC (Chen et al 2021;Petroni 2020). Considering that autophagy is also regulated by CK1α (Behrouj et al 2021), we aimed to examine the possible effect of 5-FU/D4476 co-treatment on HCT116, as a model of 5-FU resistant CRC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy (as the programmed cell death type II) is now recognized as a lysosome-dependent controlled degradation process for eliminating unwanted or malfunctioning components [ 3 , 40 ]. In a regulated manner, it enables the breakdown and recycling of cellular components, a key feature of eukaryotic cells, enabling them to renew themselves [ 41 , 42 ]. Although autophagy was previously believed to be a primitive degradation mechanism that is activated to protect the cells from starvation, it has become evident that autophagy can also contribute to the homeostasis of non-starved cells [ 43 ].…”
Section: Interplay Between Autophagy and Covid-19mentioning
confidence: 99%